A joint strategy comprising melatonin and 3-methyladenine to concurrently stimulate biomass and astaxanthin hyperaccumulation by Haematococcus pluvialis. (December 2021) - Zhao, Yongteng; Cui, Jing; Li, Qingqing; Qiao, Tengsheng; Zhong, Du-bo; Zhao, Peng; Yu, Xuya
Graphical abstract: Highlights: An induction strategy comprising melatonin and 3-methyladenine was developed. Alga biomass and astaxanthin production exhibited significant increases under the strategy. Combined application of MT and 3-MA curbed autophagy and promoted lipid synthesis. Carotenogenesis and antioxidative enzymes were upregulated by MT and 3-MA induction. The joint strategy for astaxanthin induction was not strain-specific. Abstract: Haematococcus pluvialis is a commercial microalgae used for natural astaxanthin production. This study aims to investigate the roles of melatonin (MT) and 3-methyladenine (3-MA) in regulating the cell growth and biosynthesis of astaxanthin and fatty acids under adverse conditions by H. pluvialis . Upon the dual treatments, the maximum astaxanthin concentration (46.78 mg L -1 ) was 2.39- and 1.35-fold higher compared with the control and MT treatments, respectively. Concomitantly, the combined application of MT and 3-MA suppressed autophagy but promoted the production of biomass and lipids and upregulated carotenogenesis, lipogenesis and antioxidant enzyme-related genes at the transcriptional level, which were linked with astaxanthin and lipid biosynthesis and oxidative stress. Additionally, astaxanthin exhibited a noticeable increase under MT coupled with 3-MA in the other two strains of H. pluvialis . This study proposed a potential method for astaxanthin induction and provided insights into the function of autophagy in modulating cell growth and astaxanthin synthesis.